Educação especial inclusiva nos Institutos Federais de Educação, Ciência e Tecnologia brasileiros - Mendes, Katiuscia Aparecida Moreira de Oliveira (2017)
Inserted in the research of Foundations of Educational Processes, the Inclusive Special Education research in the Brazilian Education, Science and Technology Federal Institutes, the research aims at knowing the IFs (Federal Institutes) institutional actions in order to assist the Special Education public. This research is also characterized by: a) the accomplishment of bibliographic research with the production survey regarding the theme of books, articles, essays, thesis, among others; b) 2015 Documental research, legislation study and documents produced by institutions: 2015 Management Reports and c) data evaluation through submission of electronic forms to the ones institutionally in charge of actions to assist the Special Education public. A conceptual reflection was carried out concerning the recurrent terms in the empirical data analyzed, such as: inclusion, exclusion, accessibility, equality and equity, difference and diversity praising. Political and historical aspects of the Brazilian inclusive special education and the education federal net were also addressed. By examining the aspects of the politics and legislation, it was identified an emphasis related to the architectonic accessibility aspects rather than the pedagogical issues and the specialized educational assistance, that when mentioned, do not show many details of the activities performed. The essay also highlights that the organization of the pedagogical assistance practices and the arrangements of accessibility centers depend on the local managements in each institute, that is, different movements are being configured within the federal net and the dialogue among such institutions is almost inexistent, considering the Special Education. This way, the reference related to the Tecnep Program/Action is lost while the main managing group at MEC and the Special Education start having their own trajectory inside each IF, without the need of a program, a project, actions, campaign or any other national initiative, only having the observation of the current legislation as guideline. The difficulty of the local managers group regarding hiring human resources and the offer of continuing formation is also recurrent in the data as one of the adversities mentioned for the assistance of students with NEEs.